Professionals’ Knowledge and Perceptions on Child Trafficking: Evidence from Portugal - Martinho, Gabriela (European journal on criminal policy and research, 2024)
Children who have been trafficked may experience longer-term mental health consequences with a significant impact on all life domains. Key professionals must be prepared and adopt practices that help to prevent and fight child trafficking and the harm caused. This study aims to explore the current knowledge of professionals from Portugal on child trafficking and perceptions about their practices and skills. The sample consisted of 614 professionals from justice (47.1%), education (19.4%), social (18.9%), and health care (14.7%) areas who completed an online survey. Professionals were more knowledgeable about forms of exploitation and less about victims' profile. Professionals who had direct contact with and/or training in human trafficking presented more knowledge and positive perceptions about their practices and skills. This study aims to raise awareness and develop informed training programs based on professionals’ needs and challenges.